Síntese, caracterização e avaliação do potencial bactericida do composto tetrafluorborato de aquotrisonicotinaminocobalto (II)- [Co(H2O)(isn)3](BF4)2 - Galvão, Anderson Dourado (2017)
In this work the isonicotinamide was coordinated to the Cobalt ion in oxidation state +2. A new coordination compound of Cobalt and isonicotinamide, [Co(H2O)(isn)3](BF4)2, was synthesized and described. The compound was characterized by thermoanalytical techniques TG-DTG and TG-DSC, where it was possible to propose the mechanism of thermal decomposition. It was also possible to determine the solubility of the material and the electrical nature of the chemical species synthesized by means of spectroscopy in the medium infrared region (FTIR). The bactericidal activity of [Co(H 2O)(isn)3](BF4)2, CoCl2 and free Isonicotinamide was tested for the bacteria Streptococcus mutans (Gram +) and Escherichia coli (Gram -) and the synthesized compound showed to be sensitive For both bacteria.